Understanding territorial inequalities in decentralised welfare systems: early childhood education and care system expansion in Croatia (Public Sector Economics - submission site, 2023)
The decentralised provision of social services raises concerns about availability of services in different geographical areas, particularly in low- and middleincome countries with weak governance and fiscal redistributive capacities. Yet the interconnection of different decentralisation regimes and territorial inequalities in the provision of social services remains underexplored. This article engages with one aspect of this puzzle, the implications of the fiscal conditions on exacerbating (or overcoming) territorial inequalities in services provision. Using the Croatian system of early childhood education and care (data for the 2005-2018 period) as an empirical lens, the article shows that in the absence of a well-established policy and fiscal framework sensitive to regional inequalities in administrative and fiscal capacities, decentralised systems can only institutionalise territorial inequalities in services provision. Next to the legal entitlement to a certain service, inter-territorial fiscal equalisation policies are crucial in overcoming fragmentation in social rights along territorial lines.